A conceptual analysis of brand intimacy on social media platforms. (18th August 2018) - Almubarak, Alanoud F.; Pervan, Simon J.; Johnson, Lester W.
Abstract: The nature of brand intimacy in the context of social media-based brand communities (SMBBCs) remains unclear. This paper aims to explore whether reciprocal factual and emotional self-disclosure can lead to brand intimacy in such a community; whether brand intimacy generates valued marketing outcomes, including attitudes, intentions and behaviours; and what external and internal factors motivate and enable reciprocal factual and emotional disclosures on social media platforms. A review of the relevant literature suggests that reciprocal disclosure may lead to brand intimacy in this context. For marketers, brand intimacy is important for strengthening resistance to negative information, and enhancing positive word-of-mouth, loyalty intentions, purchase intentions and brand passion, as well as developing effective marketing strategies. The degree of anonymity and the special interactivity features of SMBBCs are key external enablers of disclosure. In situations where community members internally seek relations and/or emotional support from other members, they tend to disclose their emotions. Members who internally seek social validation and/or self-expression tend to both disclose, factually and emotionally. Such a conceptual understanding of the importance of brand intimacy, paired with a number of propositions for empirical work, can serve to guide future research into this important field.